2021
DOI: 10.1159/000516669
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Stimulus-Dependent Characteristics of Innate Immune Cells in Organ-Cultured Human Corneal Tissue

Abstract: <b><i>Purpose:</i></b> The pattern of immune cells infiltrating the corneal stroma has been extensively studied in mice, but data on human tissue have been far less elaborate. To further characterize the number and differentiation state of resident immune cells in organ-cultured human corneal tissue, we employed a comprehensive bioinformatic deconvolution (xCell) of bulk RNA-sequencing (RNA-seq) data, immunohistochemistry (IHC), and flow cytometry (FC). <b><i>Methods:</i&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In accordance with previous findings, this study demonstrated that the corneal immune cell profile changes over culture time [ 8 , 9 ], with decreasing numbers over time for almost all immune cell populations. It is well known that corneal grafts which were in culture for more than 21 days showed less subsequent rejection than grafts stored for shorter times [ 8 ], a finding which is explained by decreasing numbers of competent immune cells in the cornea with increasing time in culture [ 9 ]. Adding modulatory factors to the culture medium that affect the differentiation status of immune cells in the graft have been demonstrated to reduce the risk of rejection [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with previous findings, this study demonstrated that the corneal immune cell profile changes over culture time [ 8 , 9 ], with decreasing numbers over time for almost all immune cell populations. It is well known that corneal grafts which were in culture for more than 21 days showed less subsequent rejection than grafts stored for shorter times [ 8 ], a finding which is explained by decreasing numbers of competent immune cells in the cornea with increasing time in culture [ 9 ]. Adding modulatory factors to the culture medium that affect the differentiation status of immune cells in the graft have been demonstrated to reduce the risk of rejection [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…This ensures a thorough quality control as well as detailed testing for potential infectious pathogens before transplantation. It is well known that organ culture influences donor corneas, with most of the evidence being focused on the effect of culture conditions on endothelial cell density and corneal graft survival after transplantation [ 8 , 9 ]. However, apart from that, it is still largely unknown which other molecular processes may be altered by corneal tissue culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for IR include properties of the graft (e.g., antigen mismatch, storage time in organ culture [9]) and features of the recipient [10,11]. Most importantly, vascularization of the graft bed leads to enhanced trafficking of antigen-presenting cells as well as adaptive immune cells and thus increases the risk of graft rejection.…”
Section: Immune-mediated Corneal Graft Rejection In Keratoplastymentioning
confidence: 99%